Mature Twin Neonates Exhibit Oxidative Stress via Nitric Oxide Synthase Dysfunctionality: A Prognostic Stress Marker in the Red Blood Cells and Umbilical Cord Vessels - Payal Chakraborty; Krisztina N. Dugmonits; Hajnalka Orvos; Edit Hermesz (MDPI AG, 2020)
Intrauterine hypoxic condition increases the generation of reactive oxygen species and fetal oxidative stress. Multiple pregnancy always bears an additional oxidative stress condition with severe complications, such as prematurity, structural abnormalities, delayed development and low birthweight. The umbilical cord (UC) vessels, along with circulating fetal red blood cells (RBCs), highly determine the oxygenation status of fetus and regulate the feto-placental circulation. As UC lacks innervation, the activation of the endothelial nitric oxide synthase (NOS3) is fundamental for proper NO production. Therefore, we aimed to study the NOS3 activation pathways along with damages to macromolecules in the endothelium of UC vessels and RBCs of mature non-discordant twins, in connection to major differences in their birth weight. We provide evidence that, under severe hypoxic conditions such as twin pregnancy, the NOS3-related NO production pathways are altered both in UC vessels and RBCs; moreover, the extent of changes is highly birthweight-specific. Furthermore, macromolecular damages are prominent in the RBCs and arteries compared to the vein, with a similar increase in the Arginase1 level, which is believed to play a role in NOS3 functionality, resulting in endothelial dysfunctionality, which might have relevance to the major etiologies of cardiovascular diseases in later life.